Islamic far east ethnogenesis of Philippine Islam - Donoso, Isaac (University of the Philippines Press, 2013)
Islam is a universal civilization built on the foundations of the classical world that has spread to the four corners of the earth. This book, Islamic Far East: Ethnogenesis of Philippine Islam, is a preliminary attempt to integrate/unify the Islamization of the North, South, West, and East into one worldwide phenomenon, and locate the beginnings of Islamization in the Philippines within an Islamic historical framework.